A prospective randomised controlled trial comparing three alternative bearing surfaces in primary total hip replacement. - Nikolaou, V S; Edwards, M R; Bogoch, E; Schemitsch, E H; Waddell, J P (J Bone Joint Surg Br, 2012)
The ideal bearing surface for young patients undergoing total hip replacement (THR) remains controversial. We report the five-year results of a randomised controlled trial comparing the clinical and radiological outcomes of 102 THRs in 91 patients who were < 65 years of age. These patients were randomised to receive a cobalt-chrome on ultra-high-molecular-weight polyethylene, cobalt-chrome on highly cross-linked polyethylene, or a ceramic-on-ceramic bearing. In all, 97 hip replacements in 87 patients were available for review at five years. Two hips had been revised, one for infection and one for peri-prosthetic fracture. At the final follow-up there were no significant differences between the groups for the mean Western Ontario and McMaster Universities osteoarthritis index (pain, p = 0.543; function, p = 0.10; stiffness, p = 0.99), Short Form-12 (physical component, p = 0.878; mental component, p = 0.818) or Harris hip scores (p = 0.22). Radiological outcomes revealed no significant wear in the ceramic group. Comparison of standard and highly cross-linked polyethylene, however, revealed an almost threefold difference in the mean annual linear wear rates (0.151 mm/year versus 0.059 mm/year, respectively) (p < 0.001).
Keywords: Adult; Arthroplasty, Replacement, Hip; Ceramics; Chromium; Cobalt; Female; Follow-Up Studies; Hip Prosthesis; Humans; Male; Middle Aged; Osteoarthritis, Hip; Polyethylene; Prospective Studies; Prosthesis Design; Prosthesis Failure; Severity of Illness Index; Treatment Outcome; Young Adult